2007
DOI: 10.1128/mcb.00177-07
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Analysis of Recombination Signal Sequence Configuration in the RAG1/2 Synaptic Complex

Abstract: The assembly of the gene segments coding for the variable portions of lymphocyte antigen receptors (immunoglobulins and T-cell receptors) occurs via a somatic recombination reaction known as V(D)J recombination. This process is mediated by two lymphoid cell-specific factors, RAG1 and RAG2 (recombination-activating gene products), that perform DNA cleavage at a pair of recombination signal sequences (RSSs) flanking the coding segments to be joined. RSSs consist of short palindromic heptamer and A/T-rich nonamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 42 publications
4
26
3
Order By: Relevance
“…Indeed, we measured an AmCyan-NtWLIM1 lifetime of 2.7560.07 nseconds, corresponding to a FRET efficiency of 2.8% (Fig. 5C), a value below the typical 5% significance threshold (Ciubotaru et al, 2007). Together, these data confirm the BiFC analyses and provide compelling evidence that NtWLIM1 self-associates along the actin cytoskeleton.…”
Section: Ntwlim1 Self-associates Along the Actin Cytoskeletonsupporting
confidence: 77%
“…Indeed, we measured an AmCyan-NtWLIM1 lifetime of 2.7560.07 nseconds, corresponding to a FRET efficiency of 2.8% (Fig. 5C), a value below the typical 5% significance threshold (Ciubotaru et al, 2007). Together, these data confirm the BiFC analyses and provide compelling evidence that NtWLIM1 self-associates along the actin cytoskeleton.…”
Section: Ntwlim1 Self-associates Along the Actin Cytoskeletonsupporting
confidence: 77%
“…In addition, fluorescence resonance energy transfer techniques have recently been applied to examine the orientation of DNA strands within the synaptic complex. The data obtained from these experiments led the authors to favor a model in which the RSSs adopt a bent and crossed configuration in the synaptic complex, although an alternative model in which synaptic complexes containing RSSs in parallel and antiparallel configurations assemble with similar frequency could not be formally excluded (8). For most in vitro biochemical studies, the synaptic complex has been assembled by incubating the RAG proteins with a pair of oligonucleotide substrates, one containing a 12RSS, and one containing a 23RSS.…”
mentioning
confidence: 99%
“…The effect of RAG1/2 complex binding to RSS DNA was previously addressed using biochemical and biophysical techniques (19,20,22,26) and more recently visualized within the PC in structural analysis (see SI Discussion) (14). These studies indicated that binding of HMGB1 and RAG1/2 induced bending in both the 12RSS and 23RSS DNA substrates as well as in each substrate within the PC.…”
Section: Discussionmentioning
confidence: 99%